Effectiveness of postoperative elemental diet (Elental®) in elderly patients after gastrectomy - Ohkura, Yu (World J Surg Oncol, 2016)
BACKGROUND: We aimed to investigate the efficacy of postoperative early intervention with an elemental diet to reduce weight loss and enhance recovery after gastrectomy. Nutritional status and gastrointestinal immune function tend to worsen, and postoperative weight loss is inevitable in these patients; therefore, improvement in their postoperative condition is important, especially in gastric cancer patients aged ≥80 years. METHODS: Clinical outcomes and postoperative nutritional status were compared between 21 and 22 consecutive elderly patients aged ≥80 years who underwent distal gastrectomy before and after the introduction of postoperative oral elemental diet (Elental®, 300 kcal/day), respectively, between October 2011 and June 2016. RESULTS: A significant reduction in postoperative complications was noted in the nutrition support group (N-group) as compared with the control group (C-group). In particular, the prevalence of systemic complications was significantly lower in the N-group (33.3 vs. 4.5 %, p = 0.015), whereas no significant difference was observed in the prevalence of locoregional complications. The percentage of weight loss and reduction in BMI from 1 month to 1 year after surgery was significantly lower in the N-group (p = 0.012 each). The nutrition status (albumin, total protein, hemoglobin, and C-reactive protein levels) at 1 month after surgery showed improvements (p = 0.005, p = 0.048), and hospital stay was decreased in the N-group as compared to the C-group (16.0 vs. 12.5 days, p = 0.041). CONCLUSIONS: Early intervention with an elemental diet after distal gastrectomy is valuable for reducing perioperative weight loss and improving nutritional management and may be associated with enhanced postoperative recovery in elderly patients.